OPPRESSION AGAINST INTELECTUAL PROPERTY RIGHT IN MARC ABRAHAM’S FLASH OF GENIUS (2008): A MARXIST APPROACH - KURNIAWAN, TRI (2010)
This research paper is primarily intended to identify how the oppression against intellectual property right is portrayed in Marc Abraham’s Flash of Genius viewed from Marxist’s perspective, and to analyze the movie based on its structural elements. In analyzing the movie, the writer uses qualitative study. The data are collected by using two kinds of techniques: documentation and library research. The technique of data analysis is descriptive analysis. The research significance is to give contribution to the body of knowledge, particularly the literary study on Marc Abraham’s Flash of Genius. The result of analysis confirms as follows. First, based on the structural analysis, Flash of Genius as literary work has inseparable structural elements and they are related to each other and building a good unity. Second, based on the Marxist analysis, it is apparent that in this movie Marc Abraham illustrates the social phenomena of oppression against intellectual property rights. In this movie Marc Abraham criticizes the tendency of using power by the capitalist to oppress the proletariat.